1992
DOI: 10.1159/000236088
|View full text |Cite
|
Sign up to set email alerts
|

Antiasthmatic Effects of <i>Galphimia glauca</i>, Gallic Acid, and Related Compounds Prevent Allergen- and Platelet-Activating Factor-Induced Bronchial Obstruction as well as Bronchial Hyperreactivity in Guinea Pigs

Abstract: A methanolic extract from Galphimia glauca (320 mg/kg, orally) inhibited acute bronchial reactions to allergen (ovalbumin, 10 mg/ml) and platelet-activating factor (PAF, 1 μg/ml) inhalation challenges, but not to histamine or acetylcholine in spontaneously breathing guinea pigs. Furthermore, the PAF-induced bronchial hyperreactivity was markedly reduced. Gallic acid and related compounds as well as the flavonoid, quercetin, were identified as active compounds. Gallic acid, methyl gallate and quercetin showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 9 publications
0
30
0
3
Order By: Relevance
“…Furthermore, fl avonoids suppress the production of Th2-type cytokines by activated human basophils [43]. Quercetin and isoquercitrin have been shown to inhibit the bronchial obstruction induced by different stimuli in models of allergic asthma [17,18]. However, the anti-infl ammatory activity of quercetin and isoquercitrin has never been studied in a murine model of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, fl avonoids suppress the production of Th2-type cytokines by activated human basophils [43]. Quercetin and isoquercitrin have been shown to inhibit the bronchial obstruction induced by different stimuli in models of allergic asthma [17,18]. However, the anti-infl ammatory activity of quercetin and isoquercitrin has never been studied in a murine model of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that quercetin and isoquercitrin, respectively, reduce PAF-induced and leukotriene-induced bronchoconstriction in a murine model of asthma [17,18]. Therefore, it is possible that quercetin and isoquercitrin inhibit PAF and leukotriene production in cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic extract of Galphimia glauca showed antiallergic activity in rodents due to tetragalloylquinic acid and other compounds (Neszmélyi et al, 1993). Methanolic extracts inhibit acute bronchial reactions to allergens and platelet-activating factor (PAF) in guinea pigs (Dorsch et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that methanolic extracts obtained from this plant species possess an anxiolytic effect comparable to that of lorazepam [8][9][10][11]. Due to its anti-allergic effects, Galphimia glauca is also used to treat allergies [12,13]. The use of Galphimia glauca had already become established in homoeopathic practice before the first proving of the substance was conducted.…”
Section: Introductionmentioning
confidence: 99%